2014
DOI: 10.4103/1596-3519.142281
|View full text |Cite
|
Sign up to set email alerts
|

Human immunodeficiency virus screening in rural communities of Rivers State, Nigeria: Challenges and potential solutions

Abstract: This study highlights the persistence of low HIV testing culture in rural settings in Nigeria and underscores the need that HIV programs should look beyond the healthcare settings and involve the communities, using home and community-based testing approaches in order to expand HIV testing access.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Health facility target numbers for new PWH diagnoses and ART initiations were commensurate with planned testing and treatment linkage scale-up, higher than the total number of people seeking care in health facilities. Moreover, rural populations and populations at risk for HIV acquisition may not seek care in health facilities in Nigeria, whether because of distance, cost, or dissatisfaction with services [5][6][7]. In other sub-Saharan African settings, community-based testing increases testing coverage among youth [8], and when coupled with immediate ART for those testing positive, is associated with retention in care among men [9].…”
Section: Discussionmentioning
confidence: 99%
“…Health facility target numbers for new PWH diagnoses and ART initiations were commensurate with planned testing and treatment linkage scale-up, higher than the total number of people seeking care in health facilities. Moreover, rural populations and populations at risk for HIV acquisition may not seek care in health facilities in Nigeria, whether because of distance, cost, or dissatisfaction with services [5][6][7]. In other sub-Saharan African settings, community-based testing increases testing coverage among youth [8], and when coupled with immediate ART for those testing positive, is associated with retention in care among men [9].…”
Section: Discussionmentioning
confidence: 99%
“…4 Another study evaluated the challenges of HIV screening in Port-Harcourt, Rivers state found that the major barriers to HIV testing were poor HIV risk perception, fear of stigmatization and other negative consequences of being HIV positive. 6 In Enugu, Nigeria, unwillingness to the screen was associated with the feeling of not being at risk, fear of a test outcome (positive result) and the cost of the test. 17 The result of a study conducted in Burkina-Faso revealed that the poor of positive outcome was the major reasons why people were unwilling to screen.…”
Section: Discussionmentioning
confidence: 99%
“…All these reason makes the women more vulnerable to HIV than men. 6 Disproportionate HIV infection among women have been reported in Nigeria: 55.6% of the 1.8 million infected adults in 2018 were women. 20 Also, studies have shown that new infections among women have almost double that of men 20 , which has been attributed to certain factors such as violence, or rape against women and the violation of women's human rights.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations